The Effect of the Excess Titanium Content on the Microstructure of Al – Si Foundry Alloys - Bubenkó, Marianna; Fegyverneki, György; Molnár, Dániel; Tokár, Mónika (International Journal of Engineering and Management Sciences, 2019)
Grain refining is an important technological step for the nucleus growth of the melt, in order to increase the number of nuclei, to improve mechanical properties (tensile strength, yield strength, hardness, elongation), feeding conditions and to decrease the tendency of hot tearing and the degree of sintering. [1][2] The aim of the experiments was the determination of the grain refining effects of titanium (Ti) addition in the form of AlTi5B1 master alloy to the examined alloys (AlSi7MgCu0.5 – AC 42 000, AlSi9Cu3Fe0.5 – 46 500; AlSi9Cu1 – AC 46 400). The results prove that the addition of small amount of master alloy has a favourable effect on the foundry practice.